Casuismo y sistema: Indagación histórica sobre el espíritu del Derecho Indiano - TAU ANZOÁTEGUI, VÍCTOR (Historia del Derecho, 2021)
The contemporary legal system, which has prevailed in the Western world since the 19th century, has cemented a discourse and its own way of conceiving the legal sphere. Since the end of the 18th century, legalistic and dogmatic currents have relegated the legal culture of the Ancien Régime, so finely recreated by the jurists of the ius comunne. Thus, that plural and casuistic law was confined to the shelves of libraries and the shelves of archives. Using the language, doctrinal works and documents of that modern era, Víctor Tau Anzoátegui invites us to rediscover the spirit and culture in which a law was forged that was completely different from today's law. The work, divided into three main sections, explores the beliefs, ideas and mentalities of the men who developed Indian Law. To do so, it probes into the complex and varied Spanish-American society in order to unravel the criteria of a system that prevailed beyond the three centuries of Castilian rule. Casuismo y sistema is a key work for understanding a legal culture that is not limited to the laws, but which overflows and permeates an entire judicial culture; it also invites us to delve deeper into extremely topical lines of research that seek to understand the very structures of power. In short, the validity of this book invites us to rethink that nineteenth-century dogmatic redoubt on which the present-day world was attempted to be built.